2018
DOI: 10.3171/2017.4.jns162522
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of biodegradable nerve conduit against peripheral nerve adhesion after neurolysis

Abstract: OBJECTIVE Peripheral nerve adhesion caused by extraneural and intraneural scar formation after neurolysis leads to nerve dysfunction. The authors previously developed a novel very flexible biodegradable nerve conduit composed of poly(L-lactide) and poly(ε-caprolactone) for use in peripheral nerve regeneration. In the present study, they investigated the effect of protective nerve wrapping on preventing adhesion in a rat sciatic nerve adhesion model. METHODS Rat sciatic nerves were randomly assigned to one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 61 publications
(108 reference statements)
0
46
0
3
Order By: Relevance
“…Traditional polymeric nerve conduits like polyglycolic acid and polycaprolactone (PCL) are widely used in clinical practice. However, they are not excellent enough for long‐range nerve defects …”
Section: Introductionmentioning
confidence: 99%
“…Traditional polymeric nerve conduits like polyglycolic acid and polycaprolactone (PCL) are widely used in clinical practice. However, they are not excellent enough for long‐range nerve defects …”
Section: Introductionmentioning
confidence: 99%
“…To prevent adhesion and scar formation, a variety of surgical methods have been developed, such as nerve transfer [7], fascial fat transplantation [8], venous encapsulation [9], and muscle flap transplantation [10]. However, even fine surgical techniques cannot completely rule out postoperative adhesions, and the tissues may still need to be obtained from different body parts [11]. Many natural and synthetic polymers are used to prevent adhesion, such as polyethylene films, silica gel patches [12], hyaluronic acid [13], and collagen [14].…”
Section: Introductionmentioning
confidence: 99%
“…27 In a rat model designed to assess the use of nerve wraps to prevent adhesions, Shintani et al demonstrated improved electrophysiologic outcomes at 6 weeks when a polycaprolactone conduit was used as a nerve wrap in an intact nerve, compared with no wrap in an adhesion model. 28 However, this model did not evaluate the response to nerve transection and recovery, and therefore, is most applicable to the clinical situation of an external neurolysis and decompression. Kim et al wrapped bovine collagen around rat sciatic nerve repairs and evaluated fibrosis and nerve regeneration at 3 months.…”
Section: Discussionmentioning
confidence: 99%